Studi Kesesuaian Sumber Daya dengan Pelayanan Kesehatan Tradisional Rumah Sakit Pemerintah di Provinsi DI Yogyakarta, Jawa Tengah dan Jawa Timur - Suharmiati, Suharmiati; Handayani, Lestari; Kusumawati, Lulut; Angkasawati, Tri Juni (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2018)
Traditional health services (THS) in hospitals are expected to support conventional services formally applied in Indonesia. Nonetheless, heretofore there is unknown information about the suitability of the THS and existing resources. This research was conducted to analyze the suitability of resources for the means of how it is done, with the descriptive method, cross-sectional design. The sample was determined purposively by 1 (one) government hospital every regency/city that provide more than one traditional health service and operated before or since 2014. The research subject was 2 informants every hospital consisting of the unit head of traditional health services and administration staff. The results showed that most THS types were licensed, had SOPs and had appropriate resources. The existing human resources were equally good in the THS of the herb as well as the skill unit with the tools that consist of both trained and untrained physicians, diploma of traditional healers, diploma of nursing, and or high school graduates, but none of the traditional health service units had pharmacists. Types of standard herbal medicines was obtained from herbal medicine and pharmaceutical industry although in some other units also available herbs and phytopharmaca. There was a suitability of resources and treatment at the traditional health service in hospitals.